Analogue Electrical Circuit for Simulation of the Duffing-Holmes Equation - Tamaševičiūtė, E.; Tamaševičius, A.; Mykolaitis, G.; Bumelienė, S. (Nonlinear Analysis: Modelling and Control, 2008)
We describe an extremely simple second order analogue electrical circuit for simulating the two-well Duffing-Holmes mathematical oscillator. Numerical results and analogue electrical simulations are illustrated with the snapshots of chaotic waveforms, with the phase portraits (the Lissajous figures) and with the stroboscopic maps (the Poincar´e sections).
Keywords: nonlinear dynamics; chaos; electrical circuits